O Guardador de Rebanhos: Transgressão e poética do devir em Alberto Caeiro - Ferreira, Leonilce de Lara (2016)
Fernando Pessoa stands out in worldwide literature, among other features, for having staged the multiplicity of being in an extraordinarily unique way by creating a wide heteronyms gallery. Such proposition is made by the multiplication of personalities, represented by a variety of texts produced in order to justify and organize the existence of several poetic identities, from biographies, letters and poems attributed to each of the heteronyms created. Pessoa is a poet that creates new connections with each heteronym. In this sense, the aim of this study is to analyze the production of Alberto Caeiro, heteronym of Pessoa, as the poet of “becoming”. Our focus is the workThe Keeper of Flocks, whose rhizomatic characteristics lead us to a reflection on the becoming of its production. The concepts of rhizome and becoming, as well as the conceptual notions derived from them are taken from the work of Gilles Deleuze and Felix Guattari, in the volumes of the collected writings A Thousand Plateaus: Capitalism and Schizophrenia (1987). In the analysis, we will highlight the approach of nature, in which sensations and perceptions are considered superior to thinking, in a movement of becoming-nature for the human.